FOLLOW ME THROUGH INSTAGRAM: FRONT-STAGE, BACK-STAGE, AND INTIMATE-STAGE IN GIORGIA MELONI’S AND MATTEO RENZI’S PERFORMANCES OF CELEBRITY POLITICS - Starita, Giovanni Daniele; Trillò, Tommaso (AoIR Selected Papers of Internet Research, 2023)
Over the last decade, social media became an indispensable tool for political campaigning for populist political leaders, who successfully used social media to circumvent traditional media elite and establish a seemingly direct relationship with their constituents. Based on this premises and adopting the lens of “digital populism”, our study presents a visual analysis of the portraits and candid shots posted on Instagram by two Italian populist party leaders: Giorgia Meloni and Matteo Renzi. Specifically, we explore a corpus of 424 images featuring the two leaders and posted on their respective profiles during 2020 (266 for Meloni, 158 for Renzi). Our analysis mostly focuses on a crucial semiotic feature of these images: setting. Recognizing that digital photography contributes to the mutual construction of self and space, we argue that the Renzi and Meloni strategically use setting to negotiate the inherent tension between their status as celebrity politicians and the “claim to ordinariness” typical of their populist political style. Thus, we claim that the two leaders navigate this tension by selectively posting images set “on stage” (e.g., while being interviewed during a talk show), “behind the scenes” (e.g., while working in their office), or on an “intimate stage” (e.g., on a day hike with their family). In our conclusions we reflect on the notion that populism is endemic in Italian politics, suggesting its digital manifestations take different shapes depending on political narratives that charismatic leaders construct for themselves through different mixes of celebrity and micro-celebrity practices.